Breaking the cycle: unraveling the diagnostic, pathophysiological and treatment challenges of refractory migraine - Robblee, Jennifer (Frontiers in Neurology, 2023)
Background Refractory migraine is a poorly described complication of migraine in which migraine has chronified and become resistant to standard treatments. The true prevalence is unknown, but medication resistance is common in headache clinic patient populations. Given the lack of response to treatment, this patient population is extremely difficult to treat with limited guidance in the literature. Objective To review the diagnostic, pathophysiological, and management challenges in the refractory migraine population. Discussion There are no accepted, or even ICHD-3 appendix, diagnostic criteria for refractory migraine though several proposed criteria exist. Current proposed criteria often have low bars for refractoriness while also not meeting the needs of pediatrics, lower socioeconomic status, and developing nations. Pathophysiology is unknown but can be hypothesized as a persistent “on” state as a progression from chronic migraine with increasing central sensitization, but there may be heterogeneity in the underlying pathophysiology. No guidelines exist for treatment of refractory migraine; once all guideline-based treatments are tried, treatment consists of n-of-1 treatment trials paired with non-pharmacologic management. Conclusion Refractory migraine is poorly described diagnostically, its pathophysiology can only be guessed at by extension of chronic migraine, and treatment is more the art than science of medicine. Navigating care of this refractory population will require multidisciplinary care models and an emphasis on future research to answer these unknowns.